2013
DOI: 10.1016/j.mehy.2012.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the eye of the beholder

Abstract: The pathophysiological changes that occur during ischemic stroke can have a profound effect on the surrounding nerve tissue. To this end, we advance the hypothesis that retinal damage can occur as a consequence of ischemic stroke in animal models. We discuss the preclinical evidence over the last 3 decades supporting this hypothesis of retinal damage following ischemic stroke. In our evaluation of the hypothesis, we highlight the animal models providing evidence of pathological and mechanistic link between isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, there is still a question of whether the smaller peptide sequence in ProTα has neuroprotective activity. Since the retina is more accessible than other areas of the central nervous system, and retinal ischemia mimics the physiological response of ischemic stroke (Minhas et al, 2012;D'Onofrio and Koeberle, 2013;Ishikawa et al, 2013), the aim of present study was to investigate the protective activity of ProTα-derived 6-amino acid peptides using retinal ischemia model.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a question of whether the smaller peptide sequence in ProTα has neuroprotective activity. Since the retina is more accessible than other areas of the central nervous system, and retinal ischemia mimics the physiological response of ischemic stroke (Minhas et al, 2012;D'Onofrio and Koeberle, 2013;Ishikawa et al, 2013), the aim of present study was to investigate the protective activity of ProTα-derived 6-amino acid peptides using retinal ischemia model.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we suggest that stroke patients should also be screened for retinal damage as part of the disease differential diagnosis and its treatment regimen to improve the overall clinical outcome. Clinical outcomes from transplantation of stem cells in stroke, although mostly focused on repairing the brain [32][33][34][35][36][37][38][39][40] , may benefit from exploring the grafted cells deposition and function in the eye 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neuronal function and survival are very sensitive to mitochondrial dysfunction. Recently researches have shown that mitochondrial dysfunction is closely associated with retinal neuronal damage, which can be remedied by stem cell-mediated mitochondrial repair49,50 Thus, we suppose that neurotrophic treatment, visual stimulation, and mitochondrial transplantation should be incorporated in integrated therapeutic strategy for promoting retinal neuronal repair. Technical concerns also need to be taken into consideration; further studies involving a longer follow-up period and more comprehensive evaluation of visual function are warranted.We report the upregulation of SP1 and LINGO-1 expression in RGCs in the ONC-injured retina.…”
mentioning
confidence: 99%